840–820 Ma Dahongshan bimodal volcanic rocks: new constraints on the Neoproterozoic arc–back-arc basin system along the northern margin of the Yangtze Block. Issue 9 (15th May 2023) - Liu, Yu; Xu, Yang; Ali, Polat; Yang, Kun-Guang; Zhou, Qi; Wu, Pan; Yang, Zhen-Ning
ABSTRACT: The newly identified earliest part of the Sanligang bimodal volcanic succession in the Dahongshan area of the northern Yangtze Block provides insight into the role of this block in the evolution of the Rodinia supercontinent. Field contact relationships and dating indicate that these rocks are contemporaneous and formed at 840–820 Ma. The Sanligang mafic rocks have low SiO2 (40.33–48.17 wt.%) and K2 O (0.07–1.65 wt.%), high TiO2 (2.64–3.52 wt.%) contents, and low U/Th (0.33–0.38), Th/Zr (0.001–0.002), and Nb/Y (0.059–0.064) ratios with positive εNd (t) (+5.08 to +7.59). This suggests that they are formed from magmas derived from an asthenospheric mantle source that had not been modified by slab-derived materials, with a low degree of crustal contamination during their eruption. Contemporaneous felsic rocks in the study area have high SiO2 (73.1–80.0 wt.%), variable K2 O (0.63–4.39 wt.%) and Na2 O (1.73–6.54 wt.%), and low MgO (0.1–0.58 wt.%) contents and are light rare earth element enriched, with (La/Yb)N values of 1.37–2.65 and significantly negative Eu anomalies. They have A2 -type granite affinities, as evidenced by their high 10, 000 Ga/Al values (3.51–4.55) and Zr contents (285–620 ppm), and positive whole-rock εNd (t) (+6.16–+6.52), zircon εHf (t) (+9.69–+12.29) and δ 18 O (+4.82–+6.11) values, suggesting they formed by partial melting of juvenile crustal material caused by heating associated with contemporaneous mantle-derived mafic magmatism. Combining the data for these bimodal volcanic successions with other rock assemblages in the Dahongshan area indicates that this magmatism occurred in a back-arc extensional setting. This magmatism was caused by slab detachment and separation along a vertical tear during the Neoproterozoic evolution of the arc to arc–back-arc system of the northern margin of the Yangtze Block. Graphical abstract: uf0001